Health information seeking behaviour of guardians of blind children living in the rural Free State - Motseke, Molebogeng Simphiwe (University of the Free State, 2019)
Disabilities related to sight are the most common in South Africa and commonly afflict South African children (Lehlola, 2005; 2014; DSD, DWCOD & UNICEF, 2014). In addition to normal parenting tasks, guardians of children living with disabilities are faced with the need to manage uncertainties about their children’s medical, motor, intellectual and social prognosis (Barnett et al, 2003, Gona et al., 2011). Some of these uncertainties can be managed through seeking health information, which can include disability-specific information and information about specialised support that the children may need to ensure optimum development (Eleweke et al., 2008). It is, however, well documented in the literature that guardians of children living with disabilities have unmet health information needs and that these needs are worsened in rural areas by factors including poverty, lack of education, cultural beliefs and limited access to healthcare resources (Sloper, 1999; Rahi, Manaras, Tuomainen & Hundt, 2004; Jackson, Baird, Davis-Reynolds, Smith, Blackburn & Allsebrook, 2007; Skinner & Skilfkin, 2007; Lorenzo, van Pletzen & Booyens, 2015). The culture-centred approach (CCA) to health communication focuses on listening to the voices of cultural members and allowing them to enter into communicative processes by voicing alternative perspectives of health that are relevant to their context (Dutta, 2008). Adopting the tenets of the CCA, this study sought to explore the health information seeking behaviour of guardians of blind and partially blind children who live in rural areas of the Free State province and learn from them how to best meet their health information needs regarding their children’s blindness. The objectives of this study were to (1) identify the role that cultural beliefs play in the guardians’ perception of the causes of their children’s blindness, (2) identify the source(s) of health information that the guardians commonly used and (3) determine the health information source(s) that the guardians preferred and whether the reasons for those preferences were culturally bound. Individual, face-to-face, semi-structured, in-depth interviews with 22 guardians of blind and partially blind children who live in rural areas of the Free State province revealed that the guardians’ cultural beliefs shaped how they perceived the causes of their children’s blindness, which in turn influenced their eye-care seeking behaviours and decisions to seek health information. The source of health information that the guardians commonly used was faceto-face communication between themselves and members of their families and communities, religious leaders, traditional healers, allopathic healthcare practitioners and educators from the mainstream schools that their children formerly attended. The source of health information that the guardians preferred the most was face-to-face communication in their native language at central locations within their communities such as at the local clinics, churches, schools, libraries and community halls. This study found that this preference was not culturally bound but rather influenced by the guardians’ literacy levels, socio-economic status and the accessibility of resources available to them. The findings of this study also highlight the importance of understanding the influence of the three key tenets of the CCA – culture, structure and agency- on the guardians’ health information seeking behaviour. An intersectional analysis of culture, structure and agency revealed that these tenets both enable and constrain the guardians’ health information seeking behaviour. This study argues that this understanding may help increase the guardians’ access to and use of health information by allowing for the creation of culturally relevant health information material and the provision thereof through platforms that are commonly used by and easily accessible to the guardians.
Dissertation (M.A. (Communication Science))--University of the Free State, 2019
Keywords: Health communication; Childhood blindness; Health information seeking behaviour; Eye-care seeking behaviour; Culture-centred approach; Guardians